2012
DOI: 10.1111/j.1467-9922.2012.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Teachers’ Motivational Strategies on Learners’ Motivation: A Controlled Investigation of Second Language Acquisition

Abstract: While consensus exists about the critical role of learners’ motivation in second language acquisition, controlled investigations of the effects of teachers’ motivational strategies are limited. The research reported here used a quasi‐experimental design to assess the effects of motivational strategies used by Saudi English as a foreign language (EFL) teachers (N= 14) on Saudi EFL learners’ (N= 296) self‐reported learning motivation. The experimental treatment involved class‐time exposure to 10 preselected moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(110 citation statements)
references
References 30 publications
7
100
0
3
Order By: Relevance
“…Teaching methods change, is disputed, and new methods are suggested as the pendulum swings between operant conditioning and constructivist theories of education. This supports the general consensus that motivation is critical for students' learning [1].…”
Section: Introductionsupporting
confidence: 71%
“…Teaching methods change, is disputed, and new methods are suggested as the pendulum swings between operant conditioning and constructivist theories of education. This supports the general consensus that motivation is critical for students' learning [1].…”
Section: Introductionsupporting
confidence: 71%
“…But Guilloteaux & Dörnyei (2008) point out that contrasting results for different (mixed-ability) classes in the same schools strongly suggests it is the teacher doing the motivating. Their argument has been strengthened by the subsequent quasi-experimental studies in which teachers specially trained in MotS produce positive changes in their learners' motivation over the length of a course (Moskovsky et al 2012) and even generate better L2 achievement, at least when compared to 'traditional teaching' as practised in Saudi Arabia (Alrabai 2016).…”
Section: Studies Based On Dörnyei's (2001) Taxonomymentioning
confidence: 99%
“…The practical and ethical challenges involved in such research no doubt explain why quasi-experimental interventions -involving attempts to control intervening variables and gaining permission form diverse stakeholders (e.g. as in Moskovsky et al 2012;Alrabai 2016) -make up such a tiny proportion of the research reviewed in this paper, yet such studies are to be encouraged because they offer the most persuasive evidence of motivational impact. They do not need to be large-scale, as long as the intervention itself is theoretically sound and implemented consistently, and appropriate statistical procedures are used (see Rosenzweig & Wigfield (2016) for an authoritative review of motivation interventions in science, technology, engineering and maths subjects).…”
Section: Intervention Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The past research studies have confirmed that teachers who practice motivational strategies in L2 learning process can easily Influence the L2 learner's motivation. The study by Moskovsky et al (2013) conducted a study to examine the effects of motivational strategies employed by EFL teachers to stimulate the motivation of learners in context of Saudi Arabia by following framework of Dornyei (1994). The findings of this study portrayed that teacher practiced motivational strategies which highly influenced the motivation of L2 learners.…”
Section: Introductionmentioning
confidence: 99%